Learners' reflexivity and the development of an e-learning community among students in China - Zhen Li (Association for Learning Technology, 2011)
The experiences of Chinese learners on two e-learning programmes in China wereinvestigated, focusing particularly on the formation of learning communities. Datawere collected using a range of instruments to access the learners' perspectives indepth and detail. Archer's account of reflexivity as the mediating power betweenstructure and agency is applied to understanding how learners succeeded in oneprogramme in forming a learning community, through their negotiated responsesto the existing structural and cultural conditions, whereas little evidence was foundof the emergence of learning community in the other case. Further understandingemerges from reappraisal of Confucian philosophy of learning and socialrelationships, how these influenced the participants' prior learning experiencesand how they play a part in their responses to the e-learning experience.